Effects Of Pedagogical Agents’ Instructional Roles On Learners With Different Cognitive Styles In Terms Of Achievement And Motivation - Foo , Kok Keong (2010)
This study investigated the effects of pedagogical agents‟ instructional roles in an interactive agent-based multimedia learning environment on learners with different cognitive styles in terms of achievement and motivation. Two modes of pedagogical agent with different instructional roles, namely, the Expert Agent (EXA) and the Mentor Agent (MEA), were systematically designed and developed to serve the purpose of this study.